A Model of Vaccination for Dengue in the Philippines 2016–2018 - Magal, Pierre; Seydi, Ousmane; Webb, Glenn; Wu, Yixiang (Frontiers in Applied Mathematics and Statistics, 2021)
A mathematical model of the dengue epidemic in the Philippines is developed to analyse the vaccination of children in 2016-2017. Reported case data and reported mortality data from the Philippines Department of Health is used to analyze quantitatively this vaccination program. The model compares the epidemic outcomes of no vaccination of children, vaccination only of previously infected children, and vaccination of all children.